PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP DAYA ATLET DHANY’S TAEKWONDO CLUB PEKANBARU - Nilam Cahya; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is based on observations of athletes Dhany’s Taekwondo Club Pekanbaru not able to finish the match until 3 rounds which every two rounds are carried out for two minutes. Athletes easily feel tired and feel unable to do the match. And can be seen from the presentation of technical training so far is greater than physical training, in justifying the technique first. Because of the lack of physical training methods provided by the coach. The purpose of this research was to determine whether there is an influence of circuit training exercises on the endurance of Dhany’s Taekwondo Club Pekanbaru athletes. This research was conducted at the Mini Stadium of Riau University, Simpang Baru Village, Tampan District, Pekanbaru City. Timing This research was conducted in March 2019 until April 2019 with a frequency of exercise 3x in one week. The sample in this research is the population in the Dhany’s Taekwondo Club Athletes Pekanbaru, amounting to 5 people. The design of this research was pre-test post-test one group design, which was started by doing a 15-minute pre-test session, after which the sample was given a circuit training program for 11 meetings to Dhany's Taekwondo Club Pekanbaru male athletes. After that, posttest is done for 15 minutes. The data obtained were analyzed descriptively, then testing the research hypotheses that have been submitted according to the problem is: there is the influence of training circuit training (X) on increasing endurance (Y). Based on the analysis conducted, the value between the initial test and the final test of circuit training exercises on endurance with a significant level of 0.05 with degrees of freedom N - 1 (4-1). This shows that the tcount is 2,249 with a 2,132 table then accepted. Thus it can be concluded that the hypothesis which states that there is an influence of circuit training exercises on the Endurance of the Dhany’s Taekwondo Club Pekanbaru Athletes. Keywords: Circuit Training Exercises, Athlete PowerKey Words: Circuit Training Exercise, Athlete Power